ANALISIS SIKAP PERCAYA DIRI SISWA DALAM EKSTRAKURIKULER SENI TARI DI SD AL CHOIR PANGERAN JAYAKARTA - Hanalisahara Rachmanto; Yofita Sari; Arita Marini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze students' self-confidence in dance extracurricular activities at SD Al Choir Pangeran Jayakarta. Self-confidence is an important aspect of character education that supports students in expressing their abilities and interacting socially. This research uses a qualitative approach with a phenomenological method. Data were collected through observation, interviews, and documentation involving 20 students in grades 3 and 4. The results show that dance extracurricular activities play a significant role in developing students' self-confidence, which is reflected in their courage to perform, express themselves, interact socially, and follow instructions. Regular practice and performance experiences help students overcome feelings of fear, shyness, and hesitation. Thus, dance activities become an effective medium for strengthening students’ self-confidence and character development.